Economic feasibility study of Litopenaeus vannamei shrimp farming: nanobubble investment in increasing harvest productivity - Syifa Mauladani; Asri Ifani Rahmawati; Muhammad Fahrurrozi Absirin; Rizki Nugraha Saputra; Aprian Fajar Pratama; Arief Hidayatullah; Agus Dwiarto; Ahmad Syarif; Hardi Junaedi; Dedi Cahyadi; Henry Kasman Hadi Saputra; Wendy Tri Prabowo; et al. (Jurnal Akuakultur Indonesia)
This study aimed to evaluate the economic feasibility of Litopenaeus vannamei shrimp reared at 400 shrimp/m2 in 56 days of culture. The experimental design was set in an 800 m2 HDPE pond installed with nanobubble and non-nanobubble. Shrimp survival and total harvest in nanobubble treatment was increased to 92% and 2,255 kg, respectively. Economic parameters calculated in this study were Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), Break Even Point (BEP), Benefit Cost Ratio (B/C Ratio), and Sensitivity Analysis (SA). The total investment required to run this farming practice is IDR 182,887,700. Total revenue per cycle is estimated at IDR 157,850,000 with the selling price of IDR 70,000/kg of shrimp. The estimated PP is 4 cycles, with an NPV of IDR 172,329,247 projected in 10 cycles. IRR is estimated at 18% and BEP is reached after 7,058 kg production of shrimp. B/C Ratio is estimated to be 1.26 and SA showed that productivity is the most affecting parameters in the present analysis. Based on the economic study, vannamei shrimp farming associated with nanobubble system is feasible to be realized.